Hubungan Indeks Massa Tubuh terhadap Derajat Keparahan Hernia Nukleus Pulposus Lumbal Berdasarkan Gambaran Radiologi MRI di RSD Gunung Jati Cirebon Tahun 2024 - Diva Cahya Arti; Merliana Debyanti; Bambang Wibisono (KOLONI, 2026)
umbar Herniated Nucleus Pulposus (HNP) is one of the leading causes of low back pain that may reduce patients' quality of life. A high Body Mass Index (BMI) is believed to increase axial loading on the spine, accelerate intervertebral disc degeneration, and worsen the severity of HNP. Magnetic Resonance Imaging (MRI) is considered the gold standard for objectively assessing the severity of HNP. This study aimed to analyze the relationship between body mass index (BMI) and the severity of lumbar herniated nucleus pulposus (HNP) based on magnetic resonance imaging (MRI) radiological findings at RSD Gunung Jati Cirebon in 2024. This research used a quantitative observational analytic design with a cross-sectional approach. Data were obtained from medical records of patients diagnosed with lumbar HNP who underwent MRI examination between January and December 2024. The sample was selected using total sampling, resulting in 44 eligible patients. The independent variable was BMI, classified as normal, overweight, and obesity class I, while the dependent variable was the severity of lumbar HNP based on MRI radiological interpretation, classified as mild, moderate, and severe. Data were analyzed using univariate analysis and Spearman correlation test. The results showed that most patients were in the overweight category, with 19 patients (43.2%), followed by obesity class I in 16 patients (36.4%) and normal BMI in 9 patients (20.5%). The most frequent HNP severity was severe, found in 21 patients (47.7%). Spearman correlation demonstrated a significant relationship between BMI and lumbar HNP severity (p < 0.001; r = 0.775). In conclusion, higher BMI is strongly associated with more severe lumbar HNP based on MRI findings.